Polymer films as sensitive coatings for quartz crystal microbalance sensors array - Koshets, I.A.; Kazantseva, Z.I.; Shirshov, Yu.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
This work reports on the results of investigation of quarts crystal microbalance sensors coated with polybutyl methacrylate and polyvinyl formal/ethylal to wide range of volatile organic compounds. Polymer film coated sensors showed a high sensitivity and an excellent selectivity towards these compounds. Good linearity of the concentration dependence has been obtained in almost all the concentration range of volatile compounds. The detection limit of several analytes was less than 100 ppm.